Antiobesity Activity of Iles-Iles (Amorphophallus onchophyllus) Tuber Flour in Obesity Rat Model - Putri Sulistiawati; Muhtadi Muhtadi (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Obesity is a condition that occurs when the quantity of body fat tissue is greater than the total body weight than normal, or the body experiences excess fat accumulation which causes a person's weight to be far above normal. Obesity occurs because the imbalance between energy from food intake is greater than the energy used by the body. Iles-iles tuber plant from the Araceae tribe is one of the plants used as natural medicine because the nature of the plant can cause physiological activities in the human body. The purpose of this study was to determine the anti-obesity activity of Iles-iles tuber flour (Amorphophallus onchophyllus) in a model of obese Wistar rats. Iles-iles tubers contain glucomannan which is used for treatment. A total of 25 male Wistar rats were divided into 5 groups consisting of negative given 1% PGS, positive control group was given orlistat 15.6 mg/kg.BW, and 3 treatment groups were given extracts. iles-iles tuber flour doses of 25, 50, and 100 mg/kg.BW for 14 days. Previously, an increase in body mass was carried out to become obese for 21 days and then observed changes in body weight and body length of rats for 14 days, the results of which were used to calculate the Lee index. The results showed that there was no significant difference between day 21 and day 35 in all groups with a significance of p>0.05.